2008
DOI: 10.1254/jphs.08046fp
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Eleutherococcus senticosus Extracts on Amyloid β(25-35)–Induced Neuritic Atrophy and Synaptic Loss

Abstract: Abstract. Neurons with atrophic neurites may remain alive and therefore may have the potential to regenerate even when neuronal death has occurred in some parts of the brain. This study aimed to explore effects of drugs that can facilitate the regeneration of neurites and the reconstruction of synapses even in severely damaged neurons. We investigated the effects of Eleutherococcus senticosus extracts on the regeneration of neurites and the reconstruction of synapses in rat cultured cortical neurons damaged by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…In AD, neuritic atrophy and synaptic loss occur prior to the neuronal death event and may be the first trigger of the memory impairment [21]. Therefore, our group mainly focuses on herbal drugs, such as E. senticosus [4], Panax ginseng [22] and Astragalus mongholicus [23], with potential in targeting aging-related disease in the early stage [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In AD, neuritic atrophy and synaptic loss occur prior to the neuronal death event and may be the first trigger of the memory impairment [21]. Therefore, our group mainly focuses on herbal drugs, such as E. senticosus [4], Panax ginseng [22] and Astragalus mongholicus [23], with potential in targeting aging-related disease in the early stage [7].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) The EtOAc fraction (12.0 g) was separated into seven fractions (E1-E7) by silica gel column chromatography eluted with CHCl 3 -MeOH (20:1). Fraction E3 was purified using a Sephadex LH-20 column (GE Healthcare, Sweden) eluted with MeOH to give five fractions (E3.1-E3.5).…”
Section: Preparation Of Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, A. senticosus is used as a nutritional supplement and a sedative (18). A number of studies have demonstrated that A. senticosus has significant therapeutic effects on severe neurosis, fatigue, cardiovascular disease (19,20). A. senticosus can also improve the immune function (21).…”
Section: Introductionmentioning
confidence: 99%